Desmoplastic Melanomas Mimicking Neurofibromas. (December 2020) - Gerami, Pedram; Kim, Daniel; Zhang, Bin; Compres, Elsy V.; Khan, Ayesha U.; Yazdan, Pedram; Guitart, Joan; Busam, Klaus
Abstract : Abstract: Desmoplastic melanoma can be difficult to diagnose and on average have a significantly higher T stage at the time of diagnosis compared with conventional melanomas. Histologically, these tumors typically consist of spindle cells in a fibrous matrix. The spindle cells may display fibroblast and/or Schwann cell–like features. In this study, we describe the features of 12 cases of desmoplastic melanoma closely simulating neurofibroma. Although the spindle cells in these tumors may be indistinguishable from those of neurofibroma, features such as prominent fibroplasia (12/12), poor lateral circumscription (8/9), diffuse infiltration of subcutaneous tissue (7/9), and lymphoid aggregates (10/12) may be helpful clues to the diagnosis. No immunohistochemical markers were reliable in distinguishing neurofibroma-like desmoplastic melanomas from neurofibroma. Clinical follow-up was available in 8 cases, of which 4 were initially misdiagnosed as benign neoplasms and given no further re-excision. All 4 of these cases recurred; 2 of which showed transformation to a more aggressive phenotype.